Turbogenerator: Part 1: Simulation - Yu. Lezhnev, Lev; P. Tatarnikov, Alexey; A. Skvortsov, ArÑady; A. Papkin, Igor; S. Nekrasov, Aleksandr (International Journal of Engineering and Technology, 2018)
The article describes the process of developing a turbogenerator for power plants of small and distributed power generation. The analysis of the component base for the turbogenerator was carried out, and thereof a comparative analysis of possible technical solutions was conducted. The work considered the installation variants of a turbogenerator in the exhaust system, an electric machine of a turbogenerator, types of turbines of a generator. A mathematical model for computation of the output effective and geometric parameters of a turbogenerator was described. The results of computational analysis were presented, and the parameters of the turbogenerator being developed were selected. Based on the results of the work done the conclusions were madeÂ Â